Novel Sb−SnO2 Electrode with Ti3+ Self‐Doped Urchin‐Like Rutile TiO2 Nanoclusters as the Interlayer for the Effective Degradation of Dye Pollutants. Issue 5 (13th January 2023) - Man, Shuaishuai; Yin, Zehao; Zhou, Shanbin; Pameté, Emmanuel; Xu, Lei; Bao, Hebin; Yang, Wenjing; Mo, Zhihong; Presser, Volker; Li, Xueming
Abstract: Stable and efficient SnO2 electrodes are very promising for effectively degrading refractory organic pollutants in wastewater treatment. In this regard, we firstly prepared Ti 3+ self‐doped urchin‐like rutile TiO2 nanoclusters (TiO2‐ x NCs) on a Ti mesh substrate by hydrothermal and electroreduction to serve as an interlayer for the deposition of Sb−SnO2 . The TiO2‐ x NCs/Sb−SnO2 anode exhibited a high oxygen evolution potential (2.63 V vs. SCE) and strong ⋅OH generation ability for the enhanced amount of absorbed oxygen species. Thus, the degradation results demonstrated its good rhodamine B (RhB), methylene blue (MB), alizarin yellow R (AYR), and methyl orange (MO) removal performance, with the rate constant increased 5.0, 1.9, 1.9, and 4.7 times, respectively, compared to the control Sb−SnO2 electrode. RhB and AYR degradation mechanisms are also proposed based on the results of high‐performance liquid chromatography coupled with mass spectrometry and quenching experiments. More importantly, this unique rutile interlayer prolonged the anode lifetime sixfold, given its good lattice match with SnO2 and the three‐dimensional concave–convex structure. Consequently, this work paves a new way for designing the crystal form and structure of the interlayers to obtain efficient and stable SnO2 electrodes for addressing dye wastewater problems. Abstract : It′s only water and carbon dioxide : A stable and efficient Sb−SnO2 electrode is prepared by introducing rutile Ti 3+ self‐doped urchin‐like TiO2 nanoclusters interlayer. The designed TiO2‐x NCs/Sb−SnO2 electrode can mineralize dye pollutants into CO2 and H2 O through electrochemical oxidation.